RECONSTRUCTION OF THE MEANING OF WIFE BEATING LICENSE IN THE QUR’AN: TA'WIL AN UNDERSTANDING OF THE WORD ḌARABA IN SURAH AN-NISĀ’ 34 - Zulkarnaini Zulkarnaini; Miswari Miswari; Mulyadi Mulyadi (Sekolah Tinggi Agama Islam Sadra, 2023)
This article aims to redefine the word ḍaraba in the Qur'an Surah An-Nisā’ 34. Some interpreters and jurists say that beating a wife is permissible if she leaves her obligations as a wife (nushūz) on the condition that it is in the context of education and does not injure or cause injury. Some other interpreters argue that the meaning of ḍaraba is a metaphor, that is, it does not mean hitting. However, this problem does not just end because the understanding of the mufassir who interprets ḍaraba as an order to hit is clear in the language rules, namely literal meaning. Thus, the debate over the license to beat one's wife in Islam is still a polemic and Islam is still imaged as a religion that gives a license to beat one's wife. This image makes it difficult for Islam to harmonize with modern humanism and it becomes almost impossible for ethical values in Islam to be offered as part of the values of modern humanism. This qualitative research examines the literature related to the research focus and interviews religious experts, especially commentators, to solve research problems. Interpretation of the review of the word ḍaraba is carried out through text analysis using a spiritual hermeneutic approach as systematized by Abdul Hadi WM and strengthened by the understanding of religious experts through interviews. The research findings show that the spirit of Surah An-Nisā’ 34 is in accordance with the spirit of humanism, especially regarding emancipation and gender equality. But the meaning of ḍaraba needs to be resolved through spiritual hermeneutics. So, even though it has an ontological basis that is different from modern humanism, Islamic values can be in harmony with modern humanism through this approach.